STRUCTURAL EQUATION MODELING OF COCOA EXPORT PERFORMANCE IN INDONESIA (2015–2024) - Nurulita Islami Hasibuan; Elpawati; Lebba (Syarif Hidayatullah State Islamic University Jakarta, 2025)
Cocoa is a strategic commodity that contributes significantly to Indonesia’s agricultural export performance. However, its export performance has fluctuated due to global price dynamics, exchange rate volatility, and variations in export volume. This study analyzes Indonesia’s cocoa export performance from 2015 to 2024 using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The secondary data include export volume, export value, average export price, and the rupiah exchange rate against the U.S. dollar. The SEM-PLS results indicate that export volume has a strong and significant positive effect on export value (β = 0.64, p = 0.000), demonstrating that increases in export quantity play a major role in enhancing Indonesia’s cocoa export performance. Export price shows a positive but marginal effect (β = 0.28, p = 0.056), suggesting that price movements contribute to export value but are not statistically significant at the 5% level. Meanwhile, the exchange rate has a significant negative effect on export value (β = −0.47, p = 0.001), indicating that rupiah depreciation tends to suppress cocoa export performance. The model explains 74.2% of the variance in export value (R² = 0.742), reflecting strong predictive capability. These findings provide an empirical basis for formulating data-driven strategies to strengthen Indonesia’s cocoa export performance through improvements in production capacity, pricing strategies, and exchange rate stability.